Evaluación de Terapias Acústicas en Pacientes con Acúfeno: Análisis de Conectividad en Potenciales Relacionados a Eventos - Álvarez Terríquez, Andrés; Salido Ruiz, Ricardo Antonio; Ibarra Zárate, David Isaac (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The application of acoustic therapies in the treatment of patients with tinnitus is increasingly common. The main objective of these therapies is to restore the behavior of the brain pathways and structures involved in the sense of hearing to their normal condition. Brain electrical activity (EEG) is analyzed as it is one of many tools that have been used to study the underlying mechanisms of tinnitus. In this work, some characteristics that allow the detection of changes in brain connectivity 8 weeks after starting therapy in some acoustic therapies are presented. The auditory discrimination therapy or ADT, not only presented changes in the brain connectivity of the subjects who received it, but also the graph metrics used as feature values to measure this connectivity were close to the values ​​presented in the control subjects. In the other hand, the tinnitus retraining therapy TRT, also presented changes in brain connectivity; however, the graph metrics used as feature values to measure this connectivity were not close to the values presented in the control subjects.